Sustainable Practice of Knowing Medicinal Plants through Environmental Education Theme Park at RIE, Ajmer - Barthakur, B. (SCHOOL SCIENCE, 2017)
Medicinal plants belong to the earliest known health care products that have been used by mankind. In India, the earliest reference to the medicinal value of plants is found in Rig-Veda, in which a brief reference to the healing property of plants has been made. Most of the drug plants are found in the tropics growing in wild condition and are mainly used by Ayurvedic doctors, who refer to them as Jari-Butis. We observe that in the absence of proper knowledge related to the identification of medicinal plants, many plants remained either unidentified or wrongly identified. As a result, many important and precious medicinal plants are often considered as weeds and disposed off as waste. Wrong identification even lead towards more serious repercussions as they may be used wrongly in preparing medicines for which they are not recommended. In this paper, an attempt has been made to fill the above identified gaps. Medicinal plants like arborea with locally available medicinal plants will be very useful for Ayurvedic experts, teachers, students and scientists.